A comprehensive review on preparation, characterization, and combustion characteristics of microemulsion based hybrid biofuels. (January 2020) - Kumar, Himansh; Sarma, A.K.; Kumar, Pramod
Abstract: In recent years the detrimental environmental impacts and concerns of emissions from ever-increasing locomotives have motivated the scientific community to search for alternative fuels based on renewable lipids, such as microemulsion based hybrid biofuels (MHBF). Emulsification or hybrid fuel preparation process is one of the simplest among the other biofuel production processes that do not require any chemical reaction or complex chemical handling process. This article specifically reviewed various routes for the preparation of MHBF from renewable lipid (oil) sources. In other words, the exploration of the utility of vegetable oil for MHBF formulation, physicochemical properties, comparison with biodiesel, biodiesel blends and petrodiesel, phase stability and performance analysis of CI engine are the targeted focus of the article. This study has also focused on the effects of various fuel components viz. surfactants, co-surfactants, etc., upon the physicochemical characteristics of MHBF. The microexplosion phenomenon that describes the actual combustion has been illustrated. The stability assurance of MHBF is directly influenced by the hydrophilic-lipophilic balance (HLB) value. The engine performance parameters viz., brake specific fuel consumption, mechanical, volumetric and overall efficiency have been reviewed and found that these values are comparable to the biodiesel blends with petrodiesel and pure petrodiesel. Emissions reported by the various researcher, however, have a positive attribute with respect to SOx, CO and NOx which are always lowest, while using MHBF in comparison to biodiesel and petrodiesel, in contrast to large emissions of thermal NOx in biodiesel. Unburnt hydrocarbon (UHC) is however in the higher side than biodiesel blends and petrodiesel which is manageable with increasing load. It can be ascertained from the review that MHBF can eventually replace the other renewable liquid fuel formulation in due course of time for CI engines in agro-farming machinery or even in heavy-duty vehicles attributed to the simplicity of preparation process. Graphical abstract: Image 1 Highlights: Preparation of microemulsion based hybrid biofuels from lipid and comparative study with biodiesel and petrodiesel. Effects of surfactants and co-surfactants in the overall properties of MHBF formulation. Ternary diagram for phase stability of MHBF and dependency on HLB value. Illustration of microexplosion phenomenon during MHBF combustion. Studies of engine performance, combustion and emission profiles with different MHBF formulations.